Cross-linguistic analysis of pitch range and its influence on perceived speech friendliness - Jekiel, Mateusz; Malarski, Kamil (My University, 2015)
Intonation is an important cue in evaluating speech of other speakers. Studies have shown how pragmatically meaningful it is (Grabe et al. 2003). Apart from intonational contours that may be interpreted differently depending on the context, pitch range has been named a speech parameter that is especially conducive to judging whether a speaker sounds friendly or unfriendly. Chen, Rietveld and Gussenhoven (2001) compared pitch range in Dutch and English, concluding that the latter is perceived as more friendly than the former due to its larger pitch range. This conclusion has led us to investigate the status of Polish in this analysis. In the present study, we recorded two adult male native speakers of Dutch, English and Polish and compared their pitch span and register (Ohala 1983). English was found to have a wider pitch range than Dutch, similarly to the previous study, while Polish was found to have a wider pitch range than Dutch but narrower than English. In the second part of the experiment, our subjects will evaluate how friendly the speech recordings will sound to them. Apart from raw speech samples, we have prepared modified recordings using Praat (Boersma and Weenink 2013), where both pitch span and register were set at the same levels across all speakers. We have prepared an online survey, comprising of a set of randomly ordered recordings of Dutch, English and Polish declarative, lexically identical sentences, both raw and acoustically modified. The participants (at least 20 native speakers of Dutch, English and Polish) will assess the speakers in terms of friendliness using a sevenpoint Likert scale. The survey will be preceded by a questionnaire concerning participants’ L1 and L2, age, gender, etc. Our hypotheses are that 1) the scores for the modified recordings will differ from the unmodified ones, signifying that pitch range is the main criterion for judging whether a speaker sounds friendly or unfriendly, 2) Dutch will be perceived as the least friendly due to its narrow pitch range, 3) Polish will be perceived as less friendly than English. Polish has rarely been featured in language attitude studies so far, hence, it is especially interesting to see how it scores in relation to English and Dutch. If the intermediate status of Polish pitch patterns is confirmed, yet another evidence will be obtained in the support of the view that pitch is the primary cue for determining speech friendliness.
Keywords: English; Polish; Dutch; Pitch range; Intonation; Language attitudes